CONSUMER BEHAVIOUR TOWARDS DURABLE AND NONDURABLE GOODS IN PERAMBALUR TOWN - JAYASRI, Mrs. R.; Chandrasekar, Dr.M. (IJRDO - Journal of Business Management, 2017)
The purchasing is done by keeping all these factors in mind. Today, price is not the only consideration as it was a few years back when prices played a major role in purchasing. The automobile industry in general and two wheeler industries in particular have shown a tremendous growth over the recent years. Tomorrow’s consumer will focus more on technology and credit purchase. To become a successful producer of milk products, they should think about price, quality and health consciousness of those products. Offers, gifts, price discount etc, can be given to attract more customers. This article paper highlights the consumer behaviour on durable and non-durable goods.